Additional impact on muscle function when treating active rheumatoid arthritis patients with high alfacalcidol doses - Simić Pašalić, Katarina; Gošić, Katarina; Gavrilović, Anđela; Vojinović, Jelena (Vojnosanitetski pregled, 2017)
Background/Aim. Hormone D (vitamin D) plays an important role in immunoregulation and musculoskeletal metabolism. The aim of this study was to assess the impact of alfacalcidol (ILD3) or prednisone use on muscle function and disease activity in active rheumatoid arthritis (RA). Methods. The study included 67 RA patients with the active disease, disease activity score (DAS28) > 3.2, on the highest tolerable methotrexate (MTX) dose during last 3 months. Data collected were: DAS 28, muscle function tests [chair rising test (CRT) timed up and go (TUG), 6 minutes walk (6MWT), tandem walk (TW)], efficacy and safety laboratory tests. At enrollment, patients were randomly assigned to three-month supplementation with 1 μg (group A1) or 2 μg (group A2) or 3 μg (group A3) of 1αD3 daily or prednisone (group C) 20 mg daily, for the first month and 10 mg afterward, in addition to MTX. Results. After the treatment, we found highly significantly reduced disease activity in all four treatment arms (DAS28 p < 0.01). 1αD3 2 µg (A2 group, n = 19) treated patients significantly improved muscle function (TUG, 6MWT), while 1αD3 3 µg treated (A3, n = 16) improved 6MWT (p < 0.05), and CRT (p < 0.01). Serum 25(OH)D3 significantly decreased in the group C (p < 0.01), in contrast to its changes obtained in alfacalcidol treated ones. Conclusion. 1αD3 2 μg and 3 µg daily is as effective as prednisone (mean 13.3 mg daily) in RA activity control and also has the additional favorable impact on muscle function.
Keywords: arthritis; rheumatoid; alfacalcidol; muscles; disease progression